epr, which encodes glycylglycine endopeptidase resistance, is homologous to femAB and affects serine content of peptidoglycan cross bridges in Staphylococcus capitis and Staphylococcus aureus. - Sugai, M (1997)
Staphylococcus capitis EPK1 produces a glycylglycine endopeptidase, ALE-1 (M. Sugai, T. Fujiwara, T. Akiyama, M. Ohara, H. Komatsuzawa, S. Inoue, and H. Suginaka, J. Bacteriol. 179:1193-1202, 1997), which hydrolyzes interpeptide pentaglycine chains of cell wall peptidoglycan of S. aureus. Characterizations of the enzyme activity and cloning of ale-1 revealed that ALE-1 is very similar to prolysostaphin produced by S. simulans bv. staphylolyticus. Strain EPK1 is resistant to lysis by ALE-1 and by lysostaphin. A gene that renders the cells resistant to glycylglycine endopeptidase (epr) was found 322 bp upstream of and in the opposite orientation to ale-1. The deduced amino acid sequence of epr showed similarities to FemA and FemB, which have been characterized as factors essential for methicillin resistance of S. aureus. Inactivation of either femA or femB causes decreased resistance to methicillin, increased resistance to lysostaphin, and decreased glycine content in the interpeptide chains of peptidoglycan. Therefore, femAB is suggested to be involved in the addition of glycine to pentapeptide peptidoglycan precursor. S. aureus with epr on a multicopy plasmid had phenotypes similar to those of femAB mutants except that it did not alter resistance level to methicillin. These results suggest that epr and femAB belong to the protein family involved in adding amino acids to the pentapeptide peptidoglycan precursor and that epr is involved in the addition of serine to the pentapeptide.